The Relationship Between Instructors’ Transformational Leadership Style And Their Job Satisfaction In Nursing Science Faculty, University Of Somalia - ALI, LEILA ISMAIL; Banks, Jerome (Scholar: Human Sciences, 2019)
This study investigated the relationship between instructors’ transformational leadership style and their job satisfaction in nursing science faculty, University of Somalia. This study aimed (1) to identify the degree in which transformational leadership style is used by the instructors; (2) to determine the satisfaction level of the instructors; and lastly (3) to examine the relationship between instructors’ transformational leadership style and job satisfaction of the nursing science instructors at University of Somalia. The study had 76 respondents, all full time instructors at the nursing science faculty and 100% of them responded to the survey. This research design was a quantitative and relationship study. A previously developed descriptive survey was used to investigate the Nursing Science department. The researcher used a statistical software program to analyze the collected data. This study found that the degree in which instructors use transformational leadership style was high, the instructors were overall highly satisfied with their job, and that there was a positive significant relationship between instructors’ transformational leadership style and their job satisfaction in nursing science faculty at the University of Somalia.